SISTEM PENGELOLAAN LABORATORIUM FISIKA UNTUK MEWUJUDKAN PELAKSANAAN PRAKTIKUM YANG EFISIEN - Nyoto Suseno; Riswanto Riswanto (Jurnal Pendidikan Fisika, 2017)
The Indeavorings’ problem of SMA physics laboratory are: lack competence human resource, coordinator of laboratory is as the second teacher job, the laboratory hasn’t been managed well, so far the laboratory cannot been used optimum. To overcame this problem, there is conducted guidance tacnical of laboratory workers, and workshop management of labarotory. The stap include: guidance tacnical for human resource, workshop of manual laboratory management, inventory and labeling, workshop of schedule arrangement, SOP and the implementation. The result are: 1) in general, the physics laboratory of SMA in Metro have fulfilled the infastruture standar, 2) lack of human resource, 2)good management can help the physics experements a run efficient based on the schedule. The problem found that the teachers are difficult to look for the materials and their spacification, so that needed improvement to laboratory management based on ICT